Eksplorasi Fenomena Tax Avoidance pada Perusahaan Sektor Teknologi di Indonesia - Bimantara, Aryadi; Dimar Alam, Muhammad (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study examines the influence of profitability, sales growth, capital intensity, and earning persistence on corporate tax avoidance. A quantitative approach was employed using secondary data derived from company financial reports. The population consists of all technology sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sample was selected using a purposive sampling technique, and hypothesis testing was conducted through panel data regression analysis. The results show that profitability and capital intensity have a positive effect on tax avoidance practices, while sales growth and earning persistence have no significant influence. These findings contribute to a broader understanding of the factors influencing tax avoidance behavior among companies in the technology sector.